2023
DOI: 10.1039/d3cc01101a
|View full text |Cite
|
Sign up to set email alerts
|

A novel near-infrared fluorescent probe for the imaging of viscosity in cells and tumor-bearing mice

Abstract: A near-infrared fluorescence probe (IC-V) for detecting viscosity is constructed. The probe has a large stokes shift (170 nm) and an about 180-fold increase in fluorescence intensity at 700 nm....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…All three molecules (HCy-Lyso, HCy-OH, and HCy-OH-H) were fully optimized with the density functional theory (DFT) and time-dependent density functional theory (TD-DFT) method using the B3LYP-D3 density functional, which is one of the most commonly used in the published literature for studying the structural properties of organic molecules. 48,49 B3LYP-D3 functional can also achieve a remarkable improvement in the accuracy of calculated results compared to the standard B3LYP functional. Besides, the 6-311G(d) basis set is carefully selected to obtain the best concordance with the experimental results.…”
Section: Theoretical Calculationsmentioning
confidence: 98%
“…All three molecules (HCy-Lyso, HCy-OH, and HCy-OH-H) were fully optimized with the density functional theory (DFT) and time-dependent density functional theory (TD-DFT) method using the B3LYP-D3 density functional, which is one of the most commonly used in the published literature for studying the structural properties of organic molecules. 48,49 B3LYP-D3 functional can also achieve a remarkable improvement in the accuracy of calculated results compared to the standard B3LYP functional. Besides, the 6-311G(d) basis set is carefully selected to obtain the best concordance with the experimental results.…”
Section: Theoretical Calculationsmentioning
confidence: 98%
“…What’s more, in a low-viscosity environment, free rotation of SR-Xs induces nonradiative relaxation of excited state energy, which leads to the decrease of fluorescence intensity. Along with environment viscosity gradually increasing, intramolecular rotation is suppressed, resulting in a significant enhancement in fluorescence intensity . Among them, SR-T-Al exhibits a more active fluorescence response to viscosity up to 10 folds ranging from 1.0 to 1410.4 cP.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, probes 1a–d exhibited the properties of red emission, which indicated that they had the advantages of low phototoxicity and small background interference and were suitable for high-fidelity bioimaging. 25,26 The optical properties of the probes and their biological properties were investigated in this paper.…”
Section: Introductionmentioning
confidence: 99%